Reviving Tourism in Nepal: Embracing Sustainable Mountain Adventures (The Geographic Base, 2023)
This paper explores mountain tourism in Nepal, emphasizing its rich natural beauty, cultural heritage, and adventure opportunities. The primary objective is to analyze tourist flow over the years, highlighting trends of growth, decline, and recovery. The article examines the potential of mountain tourism while addressing challenges related to tourism regulation and the necessity of environmental conservation. A descriptive approach is employed to assess these trends and challenges, utilizing secondary data from reputable sources, including the National Planning Commission, the Tourism Board, the Bureau of Statistics Nepal, and various published journals and dissertations. The study conscientiously addresses the revival of mountain tourism in Nepal and the sensitive challenges linked to mountain tourism. By emphasizing the urgency of these concerns, the article advocates for the adoption of sustainability principles and the implementation of judicious management strategies to mitigate these challenges.